1993
DOI: 10.1007/bf00402272
|View full text |Cite
|
Sign up to set email alerts
|

A multiplicity of protein antigens in subcellular fractions of rat insulinoma tissue are able to stimulate T cells obtained from non-obese diabetic mice

Abstract: Type 1 (insulin-dependent) diabetes mellitus is a T-cell mediated autoimmune disease with a number of different proteins being implicated as target autoantigens. A 38 kDa protein residing in the insulin secretory granule of insulinoma tissue is recognized by T-cell clones from a newly-diagnosed Type 1 diabetic patient. We have investigated the capacity of normal rat pancreatic beta-cell extracts and various subcellular fractions of transplantable RIN tissue to induce proliferation of T cells from non-obese dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The majority of T cell responses in spontaneously diabetic animals or humans, however, appears to be to unidentified proteins of a broad range of molecular sizes (13)(14)(15)(16). Subcellular fractionation studies have suggested that the insulin-secretory granule may be a major source of such antigens (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of T cell responses in spontaneously diabetic animals or humans, however, appears to be to unidentified proteins of a broad range of molecular sizes (13)(14)(15)(16). Subcellular fractionation studies have suggested that the insulin-secretory granule may be a major source of such antigens (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for selecting microsomal membranes secretory granule components from the transplantable rat RIN insulinoma as a source of antigens to study T cells in hutnan type 1 diabetic patients was based upon our previous observations in NOD mice that this preparation contains disease-related antigens important in the T cell mediated destruction of islet beta cells [10]. We used rat insulinoma tissue to study T cell reactivity in humans since large amounts of rat insulinoma tissue were available, in which secretory granules and different membrane fractions have been well characterized [18].…”
Section: Discussionmentioning
confidence: 99%
“…These antigens remain uncharacterized. Our earlier studies showed the presence of disease-related antigens residing in the transplantable RIN insulinoma membranes that stimulated T cctls from the unprimed NOD animals [10]. There have also been other detailed studies showing ihe presence of novel, early disease-related autoantigens in insulinoma tissues recognized by T cells from young NOD animals [11], Indeed, the antigens recognized by disease-inducing, diabetogenic T cell clones have also been localized to insulinoma secretory granules [12].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations